The Influence of Digital Literacy, Game-Based Methods, and Religiosity Attitude on Zakat Knowledge in Al-Islam and Muhammadiyahan Learning - Kurniawan, Rizaludin; Priharta, Andry; Sopa , Sopa (Pelopor Publikasi Akademika, 2025)
This study aims to analyze the influence of zakat digital literacy, game methods and religiosity attitudes on zakat knowledge in Muhammadiyah High School. This research was conducted at SMA Muhammadiyah South Tangerang, Banten. The research method used is a survey method with data analysis techniques through statistical correlation tests, simple linear regression and multiple regression. The research population included 144 students in class X of SMA Muhammadiyah, with a sample of 106 students determined through multistage random sampling techniques. The research instruments include zakat knowledge tests, zakat digital literacy, game methods and religiosity attitudes. The results of the study show that zakat digital literacy, IZI Game game methods, and religiosity attitudes have a direct positive and significant influence on zakat knowledge. Digital literacy of zakat and game methods also have a significant positive effect on religiosity. The indirect influence of digital literacy on zakat knowledge through religiosity attitudes is not significant, while the indirect influence of game methods through religiosity attitudes is significant. These findings confirm that increasing zakat knowledge is more effective through interactive learning that combines digital literacy, game methods, and the development of students' religiosity attitudes.